The effect of oxytocin massage and fennel aromatherapy on milk fluidity in lactating women within the Kawalu Health Centre Working Area, Tasikmalaya - Hasanah, Nurul; Kamelia, Emma; Kartilah, Tetet (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2024)
Background : A lack of prolactin and oxytocin hormone stimulation can decrease the amount and delivery of breast milk, affecting the baby's growth and development. Oxytocin massage mixed with fennel aromatherapy is another option for improving breast milk quality and quantity. Fennel aromatherapy is a pure liquid from the fennel plant. It contains fatty acids, flavonoids, vitamins, and minerals, such as calcium, that are excellent for their relaxing effects and can enhance breast milk supply. Objectives: This study aimed to see how oxytocin massage and fennel aromatherapy affected the optimal flow of breast milk in breastfeeding women in the Public Health Centre of Kawalu working area in Tasikmalaya. Methods : Using a two-group pretest-posttest design, conduct a quasy experiment employing a quantitative approach. The intervention group used fennel aromatherapy for oxytocin massage; on the other hand, the control group used Virgin Coconut Oil (VCO) for oxytocin massage. Non-probability sampling was used, along with a simple random sampling technique. There were 19 respondents in the intervention group and 19 in the control group. Mother and baby indicators were measured using an observation sheet. Results : The paired sample t-test results in the intervention group obtained a p-value of 0.000 (p-value ≤0.05), the control group obtained a p-value of 0.037 (p-value ≤0.05), and the independent t-test results in the intervention and control groups obtained a p-value of 0.006 (p-value ≤0.05). Conclusions: Oxytocin massage and fennel aromatherapy affect the optimal flow of breast milk in nursing mothers in the working area of Kawalu Public Health Centre in Tasikmalaya. The present study explores the potential effects of fennel aromatherapy on breastfeeding mothers, specifically focusing on its impact on breast milk optimal flow and the potential role of oxytocin massage in this context.